Prevalence of Musculoskeletal Disorders among Dentists: A Comprehensive Systematic Review - Nasser Lasaf Dh Alanazi, Fayez Alhumedi Alshammari, Nasser Matar Alanazi, Ali Radhi Ali Almutairi, Farhan Faleh Alshammari, Hasan Faris H Alajmi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Musculoskeletal disorders (MSDs) have emerged as significant challenges for healthcare professionals, particularly dentists. This systematic review aims to present the prevalence of MSDs among dentists Materials and Methods: All published literature regarding MSDs in dentists were included in this study without any time constraints or other limitations. However, it was noted that there is a scarcity of studies on MSDs among dentists. Results: Findings from the reviewed literature revealed a wide range of prevalence rates, ranging from 0.5% to 70%. The prevalence of pain in various regions included: neck pain (0.7% - 15%), back pain (0.08% - 55%), wrist pain (0.005% - 48%), shoulder pain (0.08% - 50%), knee pain (0.03% - 25%), and elbow pain (0.01% - 20%). Gender did not appear to influence the prevalence rates. Comparison with similar studies indicates that the prevalence of MSDs is a significant concern in other regions as well. Conclusion: The results underscore a high prevalence of musculoskeletal issues among dentists . Thus, there is a pressing need for reliable and comprehensive epidemiological studies to better understand the underlying causes of this problem and to propose effective solutions